PENGENALAN PEMBENTUKAN JENTIK-JENTIK CILIK UNTUK PENCEGAHAN DEMAM BERDARAH DI SDN 4 LENDANG NANGKA - Patimatuzzahro; Arniati, Irma; Kurniatussolihah, Lilik; Watulummah, Siti Mira (Alpatih Harapan Semesta, 2024)
Dengue fever (DBD) is one of the main health issues in Indonesia that requires active community involvement in its prevention. The Jentik Cilik program, initiated at SDN 4 Lendang Nangka, aims to provide education and involve elementary school students as agents of change in mosquito nest eradication (PSN). This study aims to evaluate the implementation of the Jentik Cilik program and its impact on student awareness and the condition of the school environment. Using a descriptive qualitative method, the research shows that this program enhances students' understanding of PSN and results in a decrease in the mosquito larva population in the school environment. This article is expected to serve as a reference for the implementation of similar programs in other schools as part of the national dengue prevention effort.